2015
DOI: 10.1038/ncomms6987
|View full text |Cite
|
Sign up to set email alerts
|

BCL11A is a triple-negative breast cancer gene with critical functions in stem and progenitor cells

Abstract: Triple-negative breast cancer (TNBC) has poor prognostic outcome compared with other types of breast cancer. The molecular and cellular mechanisms underlying TNBC pathology are not fully understood. Here, we report that the transcription factor BCL11A is overexpressed in TNBC including basal-like breast cancer (BLBC) and that its genomic locus is amplified in up to 38% of BLBC tumours. Exogenous BCL11A overexpression promotes tumour formation, whereas its knockdown in TNBC cell lines suppresses their tumourige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
157
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 61 publications
9
157
0
1
Order By: Relevance
“…Khaled et al revealed a novel tumorigenic function of BCL11A in TNBC. In brief, BCL11A is highly expressed in TNBC, and exogenous BCL11A overexpression in TNBC promotes tumor development in vitro and in vivo [20]. These findings indicate that BCL11A might be a potential candidate for targeted therapy in TNBC.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Khaled et al revealed a novel tumorigenic function of BCL11A in TNBC. In brief, BCL11A is highly expressed in TNBC, and exogenous BCL11A overexpression in TNBC promotes tumor development in vitro and in vivo [20]. These findings indicate that BCL11A might be a potential candidate for targeted therapy in TNBC.…”
Section: Introductionmentioning
confidence: 83%
“…Previous study suggests that BCL11A acts as an oncogene in TNBC [20]. We next examined whether miR-137-mediated down-regulation of BCL11A would inhibit tumor development in TNBC cells.…”
Section: Mir-137 Inhibits Cancer Stemness Of Tnbc By Down-regulatingmentioning
confidence: 99%
“…125,126 In principle, the genetic knockout of BCL11A by targeting BCL11A coding sequence in order to create frameshift null alleles represents a potential therapeutic strategy. Roles of BCL11A in nonhematopoietic lineages, including the neural lineage, 127,128 pancreatic progenitors, 129 and the breast epithelium, 130 would not be problematic upon modification of BCL11A in autologous CD34 1 HSPCs. However, this strategy is limited by extraerythroid roles of BCL11A in the hematopoietic system, including its requirement for B-cell development 127,[131][132][133] and HSC function.…”
Section: Bcl11a Targetingmentioning
confidence: 99%
“…Recently, high expression of the functionally related protein Bcl11a was reported in Triple-negative breast cancers (18). A similar analysis of Bcl11b expression in breast cancer subtypes and comparison with a Bcl11b high signature could provide some hints whether Bcl11b contributes to breast tumorigenesis.…”
mentioning
confidence: 97%